Video over Cognitive Radio Networks When Quality of Service Meets Spectrum - Mao, Shiwen; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book focuses on the problem of video streaming over emerging cognitive radio (CR) networks. The book discusses the problems and techniques for scalable video streaming over cellular cognitive radio networks, ad hoc CR networks, cooperative CR networks, and femtocell CR networks. The author formulates these problems and proposes optimal algorithms to solve these problems. Also, the book analyzes the proposed algorithms and validates the algorithms with simulations.
Introduction -- Video over Cellular CR networks -- Video over Cooperative CR Networks -- Video over Femto CR Networks -- Video over Multi-hop CR Networks -- Conclusion and Open Problems.
Keywords: Engineering; Computer network architectures; Telecommunication; Engineering; Communications Engineering, Networks; Computer Systems Organization and Communication Networks; Signal, Image and Speech Processing